Association between body mass index and fecal calprotectin levels in children and adolescents with irritable bowel syndrome. Issue 32 (12th August 2022) - Kim, Jun Hwan; Yi, Dae Yong; Lee, Yoo Min; Choi, You Jin; Kim, Ju Young; Hong, Yong Hee; Park, Ji Young; Kim, Su Yeong; Lee, Na Mi; Yun, Sin Weon; Chae, Soo Ahn; Lim, In Seok; et al.
Abstract : Irritable bowel syndrome (IBS) is a common pediatric functional gastrointestinal disorder. It is characterized by recurrent abdominal pain and changes in bowel habits and is more prevalent in obese patients. We investigated the association between obesity and IBS in pediatric patients through fecal calprotectin testing. Patients under 18 years of age with IBS who underwent fecal calprotectin testing from January 2015 through April 2020 were retrospectively investigated. The patients were divided into groups based on body mass index (BMI): group I (BMI < 85th percentile) and group II (BMI ≥ 85th percentile). Group II was divided into group IIa, overweight (85th percentile ≤ BMI < 95th percentile), and group IIb, obese (BMI ≥ 95th percentile). Among 277 included patients, 202 (72.9%) were in group I, and 75 (27.1%) were in group II (mean calprotectin levels, 75.60 ± 103.48 vs 45.89 ± 66.57 µg/g, respectively; P = .006). There were significant differences in mean calprotectin levels between groups I and IIa (75.60 ± 103.48 vs 45.45 ± 63.38 µg/g, respectively; P = .028) and groups I and IIb (75.60 ± 103.48 vs 46.22 ± 69.59 µg/g, respectively; P = .025). There was a significant difference in mean calprotectin levels between groups I and II (85.69 ± 142.13 vs 32.04 ± 28.17 µg/g, respectively; P = .029) among patients between 6 and 12 years of age but not among adolescents aged between 12 and 18 years ( P = .139). Fecal calprotectin was lower when moderate-to-severe fatty livers were observed by ultrasound compared with normal livers (68.52 ± 97.22 vs 18.53 ± 18.56 µg/g, respectively; P = .017). Fecal calprotectin levels were higher in normal-weight pediatric IBS patients than in their obese counterparts, and this difference was more prominent in younger patients. In young children, IBS symptoms are thought to be influenced more by factors other than intestinal inflammation.